B s 0 → ℓ + ℓ − γ as a test of lepton flavor universality - Diego Guadagnoli (Journal of High Energy Physics, 2017)
Abstract We discuss a number of strategies to reduce the ℬ(B s 0 → ℓ + ℓ − γ) theoretical error, and make such a measurement a new probe of the interactions that are interesting in the light of present-day flavor discrepancies. In particular, for low di-lepton invariant mass we propose to exploit the close parenthood between ℬ(B s 0 → ℓ + ℓ − γ) and the measured ℬ(B s 0 → ϕ(→K+K−)γ). For high q 2, conversely, we exploit the fact that the decay is dominated by two form-factor combinations, plus contributions from broad charmonium that we model accordingly. We construct the ratio R γ , akin to R K and likewise sensitive to lepton-universality violation. Provided the two rates in this ratio are integrated in a suitable region that minimises bremsstrahlung contributions while maximising statistics, the ratio is very close to unity and the form-factor dependence cancels to an extent that makes it a new valuable probe of lepton-universality violating contributions in the effective Hamiltonian. We finally speculate on additional ideas to extract short-distance information from resonance regions, which are theoretically interesting but statistically limited at present.